A Monthly Indicator of Economic Growth for Low Income Countries - Stanger, Michael (IMF Working Papers; Working Paper ;, 2020)
Monthly economic indicators support policy analysis of current economic developments and forecasting. This paper presents an overview of the data and statistical requirements to develop those indicators taking into account resource constraints that LIC typically face. We review statistical procedures for developing these indicators under the System of National Accounts and propose a general procedure to derive a monthly composite indicator of economic growth in low income economies.